Geant4-based comprehensive study of the absorbed fraction for electrons and gamma-photons using various geometrical models and biological tissues - Rahman Ziaur; Rehman Shakeel Ur.; Mirza Sikander M.; Arshed Waheed; Mirza Nasir M. (Nuclear Technology and Radiation Protection, 2013)
The Geant4-based comprehensive model has been developed to predict absorbed fraction values for both electrons and gamma photons in spherical, ellipsoidal, and cylindrical geometries. Simulations have been carried out for water, ICRP soft-, brain-, lung-, and ICRU bone tissue for electrons in 0.1 MeV-4 MeV and g-photons in the 0.02 MeV-2.75 MeV energy range. Consistent with experimental observations, the Geant4-simulated values of absorbed fractions show a decreasing trend with an increase in radiation energy. Compared with NIST XCOM and ICRU data, the Geant4-based simulated values of the absorbed fraction remain within a 4.2% and 1.6% deviation, respectively. For electrons and g-photons, the relative difference between the Geant4-based comprehensive model predictions and those of Stabin and Konijnenberg's re-evaluation remains within a 6.8% and 7.4% range, respectively. Ellipsoidal and cylindrical models show 4.9% and 10.1% higher respective values of absorbed dose fractions relative to the spherical model. Target volume dependence of the absorbed fraction values has been found to follow a logical behavior for electrons and Belehradek's equation for g-photons. Gamma-ray absorbed fraction values have been found to be sensitive to the material composition of targets, especially at low energies, while for elections, they remain insensitive to them.